The headship game : the challenges of contemporary school leadership - Fidler, Brian (RoutledgeFalmer, 2004)
This book describes what it means to be a headteacher, what current headship entails and how prospective headteachers prepare themselves for headship. Underlying is the question of what could be done to support and make headship attractive.